Diseño de un prototipo de sistema de comunicación personal mediante el uso de señales de electroencefalografía (EEG) (2015)
This paper presents a brain-computer interface (BCI) designed for patients affected with Amyotrophic lateral sclerosis (ALS) or with other diseases with Bulbar-Spinal Muscular Atrophy that affect the patient interaction with the environment. By using an EEG portable (Emotiv Epoc) we acquired neural signals which were processed and used for make a choice in the initial prototype for healthy subjects. In this case, we have worked with EEG’s artifacts with the purpose of train and validate a neural network with seven different persons. With the results obtained, we can conclude that the Emotiv headset is a good alternative for the creation of technological devices, which purpose is to close the communication gap between a diseased patient and his environment.